Storage stability of popped pearl millet based ready to eat breakfast cereal - SINGH, RITU; SINGH, KARUNA; NAIN, MANJEET SINGH; SINGH, RASHMI (The Indian Journal of Agricultural Sciences, 2020)
The study was carried out for the assessment of storage stability of popped pearl millet based Ready to Eat (RTE) breakfast cereal. The RTE breakfast cereal based on popped pearl millet was developed and standardised and storage study was done under ambient conditions (25± 28.0 °C and 65 ± 10% RH) after packaging in Metalized Pouches of 1.36 mm thickness for 3 months. The RTE- breakfast cereal was evaluated for moisture, water activity (aw), Free Fatty Acids and Peroxide Value and overall acceptability at an interval of 15 days. Microbial count (yeast and mold count) were also determined during the entire period of storage. The results revealed a marginal increase in all the parameters during storage and overall acceptability value was 7.29. No significant change was noticed in the RTE – breakfast cereal and was found with acceptable attributes at ambient conditions. The study illustrated the storage stability and safety of popped pearl millet-based RTE breakfast cereal at ambient storage in metalized pouches throughout three months storage period. Consistent increase in deteriorative quality parameters (moisture content, water activity, FFA, PV) was observed during the storage period. However, no significant difference on sensory evaluation of RTE- breakfast was observed during the storage period. Although there were increases in deteriorative parameters, but none of the parameters suggested initiation of spoilage in the product. The total plate count, yeast, mould count was not detected during the storage period, further indicated safety of the popped pearl millet breakfast cereal product for consumption.